PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS HUMAN COMPUTER INTERACTION (HCI) UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA SD MUHAMMADIYAH - Isneini Eermawati; Eko Bayu Gumilar (Sekolah Tinggi Agama Islam Muhammadiyah Blora, 2022)
This research has two objectives, namely a) to find out how the development of this HCI-based learning media in increasing student learning motivation in PAI subjects at SD Muhammadiyah 1 Blora, 2) to produce HCI-based learning media in the form of applications that are feasible and to increase student learning motivation in PAI subjects at SD Muhammadiyah 1 Blora. To produce HCI-based learning media in the form of applications that are feasible and to increase student learning motivation in PAI subjects at SD Muhammadiyah 1 Blora. This type of research is Research and Development (R&D) or research and development, because this research is oriented to the products developed. The type of data obtained in this research is descriptive quantitative data supplemented by qualitative data and documentation. The data collection methods used by researchers include, a) Observation (observation), b) Interview (interview), c) Questionnaire (questionnaire), d) Documentation. The results of this research and development produce HCI-based learning media products in the form of applications that are feasible to use and can increase student learning motivation in PAI learning in class V. This can be seen from the results of the HCI-based learning media questionnaire. This can be seen from the results of the student learning motivation questionnaire which shows that when learning by using HCI-based learning media, student learning motivation increases with an average of 3.70. The results of product assessment by material experts at stage I show that the quality of the product is included in the sufficient category with an average score of 3.32, stage II is included in the excellent category with an average score of 4.73. Assessment of HCI-based learning media products by stage I media experts shows that the quality of the media is included in the good category with an average score of 3.41, stage II is included in the